Komunikasi Interpersonal Antara Ibu dan Anak dalam Menghadapi Konflik - Dewi, Putu Nanda Sukma Pradnya; Anggreni, Ni Wayan Yuli (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study discusses the dynamics of interpersonal communication between mothers and children in dealing with family conflicts. Conflict is a natural part of interpersonal relationships, but the way it is managed determines the quality of long-term relationships. Interpersonal communication is an important element because through the process of exchanging messages, mothers and children can express their feelings, understand each other's perspectives, and find an agreement that can be accepted by both parties. This study uses a qualitative approach with a literature review method to examine communication patterns, barriers, and strategies used in the conflict resolution process. The results of the study showed that open communication, empathy, emotional presence, and active listening skills greatly influenced the success of conflict management. In addition, research has found that the alignment of verbal and nonverbal messages, the use of non-judgmental language, and mutual respect can create an atmosphere conducive to dialogue. This study makes a theoretical contribution to understanding modern family relations and practical implications for strengthening communication in dealing with mother-child conflicts.